Witness Potential of Evangelical Poverty in India - Thomas Kadankavil (Journal of Dharma, 2020)
To be self-critical for a religion or a religious movement is hardly possible where the belief is not tempered by the recognition of secular values. But more often than not when a religious enth~sias: under- takes such an examination, he rather attends to the existential con- sequences of his religious belief not bei~~ seriously practis~d than to the theoretical inconsistency or acceptability of such a belief. Thus Justinian Cherupallikat, accepting a life lived under a vow which prohibits a man the free use of earthly goods as a desirable spiritual value, undertakes to survey the existential situation as regards its practice in the religious groups in the Catholic Church in his work, Witness Potential of Evangelical Poverty in India.